Elements affecting primary school teachers' digital competency in Vietnam’s northern mountainous areas - Nguyen, Chuyen Thi Hong; Thu, Huong Le Thi; Thuy, Duong Lam; Thu, Ha Nguyen Thi; Minh, Thai Doan Thi (Journal of Education and e-Learning Research, 2024)
This study aims to identify the elements that contribute to the digital competencies of primary school teachers working in the mountainous region of Northern Vietnam and assess the significance of these factors. The research sample consisted of 260 primary school teachers from this region. Exploratory factor analysis (EFA) and multivariate regression methods are used. The results of this research indicate that seven characteristics have a substantial impact on the digital abilities of teachers: ability to incorporate digital technology into teaching, conditions for digital transformation in teaching and learning activities are found to be influential, ability to create digital resources is highlighted as an important factor, ability to select teaching content with opportunities for technology usage, professional development needs of teachers, school policy and ability to select digital resources. These results offer education administrators a comprehensive understanding of the factors influencing primary teachers' digital competencies and enable them to implement strategic changes and prioritize each element. Moreover, this study provides a valuable reference for future researchers seeking to explore new research directions in this field and analyze the correlation between factors to propose solutions to develop digital competencies of primary school teachers suitable to specific contexts and conditions.